The Effects of Plant Spacing and Pruning System on Plant Performance, Yield and Quality of Bananas 'Mas' (AA) and 'Berangan' (AAA) - Mahmood, Zabedah (1991)
The study was conducted to find out the effects of spacing and pruning system on the performance of 2 cultivars of bananas, namely, 'Mas' and 'Berangan'. The trial was conducted at 2 locations: MARDI Jerangau, Terengganu and MARDI Serdang, Selangor. For both locations the highest yield of the first crop of both cultivars was obtained at 1.5m x 1.5m spacing, followed by 3 m x 1.5 m and 3 m x 3 m spacings. In Jerangau, the yield of 'Mas' at 3 m x 3 m was 9 metric tons (mtl/ha; increased to 17 mt/ha at 3 m x 1.5 m and further increased to 31 mt/ha at 1.5 m x 1.5 m . For the ratoon crops, the yield trend was quite different from the plant crop.